Effect of free cash flow, company size, and leverage on stock return with dividend policy as a moderation variable - ACHMAD FADEL FARID; AMIRUDDIN; NADHIRAH NAGU (International Journal of Multidisciplinary Research and Studies, 2023)
The purpose of this study was to analyze the effect of (1) free cash flow on stock returns , (2) company size on stock returns , (3) Leverage on stock returns (4) dividend policy in moderating free cash flow on stock returns , (5) dividend policy in moderating firm size on stock returns , (6) dividend policy in moderating free cash flow on returns stock . This research uses quantitative research methods. The sampling procedure in this study was based on a purposive sampling method, the population in this study amounted to 13 companies with 65 data. This study uses secondary data, which is obtained from the internet through the official IDX website ( www.idx.co.id ) and the official website of each company. The statistical method used to test the hypothesis is by using the SPSS statistical application. The results showed that free cash flow and firm size had a positive effect, and leverage had a negative effect on stock returns. While the moderating effect in this study, dividend policy strengthens the effect of free cash flow and firm size on stock returns and dividend policy does not moderate the effect of leverage on stock returns.